Seasonal Movements and Habitat Use of Juvenile Smooth Hammerhead Sharks in the Western North Atlantic Ocean and Significance for Management - Logan, Ryan K.; Vaudo, Jeremy J.; Sousa, Lara L.; Sampson, Mark; Wetherbee, Bradley M.; Shivji, Mahmood S. (Frontiers in Marine Science, 2020)
Upper trophic level predators dramatically impacted by fisheries include the large-bodied hammerhead sharks, which have become species of conservation concern worldwide. Implementing spatial management for conservation of hammerhead populations requires knowledge of temporal distribution patterns and habitat use, identification of essential habitat for protection, and quantification of interactions with human activities. There is little such information for the smooth hammerhead shark, Sphyrna zygaena. We used fin-mounted satellite tags to examine the movements and habitat use of juvenile smooth hammerheads, a demographic segment particularly threatened by exploitation. Six sharks were tagged off the US mid-Atlantic and tracked for 49–441 days (mean 187 ± 136 days). Sharks consistently showed area-restricted movements within a summer core area in waters of the New York Bight and a winter core area off Cape Hatteras, North Carolina, with directed movements between them in autumn. There was high overlap of shark winter core area use and the Mid-Atlantic Shark Area (MASA) – a 7 month per year, bottom-longline fishery closure – indicating that this area closure offers seasonal reduction in fishing pressure for this species. Based on timing of shark movements and the MASA closure, protection for juvenile smooth hammerheads may be increased by beginning the closure period 1 month earlier than currently scheduled. Generalized additive mixed models revealed that area-restricted movements of sharks in their summer and winter core areas coincided with high primary productivity, and elevated sea surface temperature. Consistency in use of summer and winter core areas suggests that the coastal waters of the New York Bight and Cape Hatteras, North Carolina could be considered for Essential Fish Habitat designation for this species. This study reveals the first high resolution movements and habitat use for smooth hammerheads in the western North Atlantic to inform management planning for this population.